2010
DOI: 10.1002/uog.7485
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal mesh repair of anterior and posterior vaginal wall prolapse: a clinical and ultrasonographic study

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 18 publications
0
25
0
3
Order By: Relevance
“…In comparison to the transobturator technique on sonomorphological findings [18,20,21], we found a larger part of vagina covered by the mesh. 55 % of the implanted mesh was measured at follow-up exam, in former studies conducted in our centre the Perigee and Prolift meshes showed a length after implantation of 43 %.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In comparison to the transobturator technique on sonomorphological findings [18,20,21], we found a larger part of vagina covered by the mesh. 55 % of the implanted mesh was measured at follow-up exam, in former studies conducted in our centre the Perigee and Prolift meshes showed a length after implantation of 43 %.…”
Section: Discussionmentioning
confidence: 85%
“…De Tayrac et al described the lack of sufficient support of the vaginal vault, which can lead to anatomical failure [19,20]. They also claimed dyspareunia being a result of mesh shifting caused by the lack of apical fixation [19].…”
Section: Discussionmentioning
confidence: 96%
“…Les deux patientes du groupe de ré paration prothé tique pré sentaient toutes les deux des complications du maté riel avec ré traction et exposition responsables des symptômes douloureux. Dans notre expé rience clinique et é chographique [12], les ré tractions sé vè res à un an ne concernent que 9,3 % des cas dont toutes n'occasionnent pas de douleurs pelviennes notamment spontané es comme il est l'objet dans notre é tude. Feiner et Maher [13] en analysant 17 cas de ré tractions douloureuses prothé tiques sur des kits Prolift TM identifient la majorité de ces zones douloureuses à l'union entre le corps et le dé part des bras de la prothè se, ce qui est en accord avec notre expé rience.…”
Section: Discussionunclassified
“…Mesh retraction, contraction or shrinkage is believed by some to be the cause of pelvic pain 64 , 67 and recurrence 68 . Ultrasound could be useful in diagnosing mesh ‘contraction, where the mesh appears folded and thickened instead of flat and smooth (Figure 9).…”
Section: Methodsmentioning
confidence: 99%